Syndesmis patagonica n. sp. (Rhabdocoela: Umagillidae) from the sea urchin Arbacia dufresnii (Echinodermata: Echinoidea) in Patagonia, Argentina - Brogger, Martin Ignacio (2010)
The umagillid Syndesmis patagonica n. sp. is described from the intestinal tract of the sea urchin Arbacia dufresnii, which represents a new host record for the genus. The hosts were collected from the coast of Patagonia (Argentina), and S. patagonica n. sp. is the first species of Syndesmis reported from South America. Syndesmis patagonica n. sp. can be distinguished from all other species in the genus by the possession of a stylet that is extremely short (less than 50 µm long), and a combination of other characters including the position of the testes, body size, body color and host. An updated overview of the distribution of all species of Syndesmis is also presented.